(untitled) (Research, Society and Development, 2020)
School dropout is a problem that must be tackled in every educational institution, because, in addition to the evaded student causing loss of public investment made in it, the community loses a student who could contribute professionally to their education. Thus, this study has as its general objective: to develop a management process capable of reducing dropout, and as specific objectives: to understand the factors that contribute to dropout; Know the IFPI’s strategic planning (PDI) and the institution’s objectives related to dropout, check how the institution has dealt with the dropout problem and identify solutions to reduce dropout through management processes. To meet these objectives, a qualitative research was conducted in October 2018, through a case study with 10 employees who hold different positions in the management of the Parnaíba campus of the Federal Institute of Piauí (IFPI). The research approach is qualitative and it is also classified as action research. The results of this research showed 11 main reasons for the student to evade, especially the lack of transportation, due to the campus location, a process of connection between the sectors, academic control, pedagogical sector, and others was also suggested, with supervision of the coordination.